Difference in Quality and Volatile Flavor Compounds of Zingiber officinale Roscoe with Different Drying Methods - Jiani Chen; Jinhua Wang; Yonghui Ge; Hongrui Ping; Wenxuan Liu (Journal of Food Quality)
In order to study the effect of different drying methods on the quality of ginger (Zingiber officinale Roscoe) in Guizhou Province, the study comparatively analyzed the edible quality, functional components, and volatile flavor compounds of dried ginger. The results revealed that vacuum freeze-drying (VFD) was superior to vacuum microwave drying (WAD), hot air drying (HAD), and natural drying (ND) in terms of retaining ginger color change, rehydration rate, flavonoids, and ginger spicy element. The polyphenol retention in VFD ginger was second only to that in WAD ginger. A total of 86 volatile flavor compounds were detected in fresh ginger and all four drying samples. Ester and aldehyde compounds were identified as the main flavor components in dried ginger, with variations observed among the different drying methods. Principal component analysis (PCA) and the nearest neighbor algorithm successfully distinguished the ginger samples treated with different drying methods. The aroma activity value (OAV) was calculated based on the threshold, and 12 volatile flavor compounds with OAV ≥1 were identified as the key aroma components of ginger. The aroma profiles of ginger were generally similar across the four different drying methods, among which WAD ginger exhibited distinct flavor characteristics associated with drying. This study employed physicochemical properties, active components, and GC-IMS to evaluate the effect of different drying methods on ginger, providing valuable insights for the processing and flavor quality control of drying ginger.